Mental health service use among university students with adverse childhood experiences. (13th November 2019) - Jakovljevic, M; Matejic, B; Medarevic, A; Mladenovic Jankovic, S; Neskovic, A; Tripkovic, K; Belamaric, G
Abstract: Background: Adverse childhood experiences (ACE) are a risk factor for mental health disorders and serious somatic illnesses. There is a need for preventing ACE and using mental health care by youth who experienced them. Aims of this study were to examine which ACE are related to mental health service use and to identify a scope of unrecognized needs for these services among students who had experienced abuse/neglect in childhood. Methods: Descriptive cross-sectional study was performed on a sample of 2.381 first-year students from six universities in Serbia in 2014. The survey instrument was a questionnaire developed by WHO and CDC. Thirteen ACE (covering household dysfunctionalities, abuse, neglect, peer and collective violence) and using of mental health services at least once during lifetime were assessed. Data were analyzed by univariate and multivariate logistic regression. Results: Compared to respondents without particular ACE, odds (±95% CI) of mental health service use were higher only in those with next adversities: parental divorce, OR = 2, 26 (1, 53-3, 33); suicidal/mentally ill family member, OR = 2, 21 (1, 42-3, 44); witnessing partner violence, OR = 1, 51 (1, 04-2, 18); peer violence, OR = 2, 14 (1, 51-3, 03); collective violence OR = 1, 48 (1, 05- 2, 10). Among respondents who had experienced emotional neglect, 81% have never used professional help. For physical neglect, physical and psychological abuse this percentage was 83%. Conclusions: The study highlights ACE associated with mental health service use and shows a significant presence of unrecognized needs for these services. There is need for: determining barriers in this area and formulation of effective health promotion strategies; more consistent application of legislation; conducting screening on child abuse/neglect in families with a higher risk for them. Key messages: High share of youth with childhood adversities remains without help of mental health specialists.It opens the issue of barriers on the side of youth as well as on the side of health system and society Considering consequences of adverse childhood experiences, there is need for comprehensive public health interventions in order to increase mental health service use among young people with ACE.